Training on interactive learning media for elementary school teachers in Purworejo District - Siska Desy Fatmaryanti; Amanda Bella Sasmita; Hasna Khoirunnisa; Adera Maulidya; Anandha Meylia; Tegar Agung Prihantoro (Universitas Muhammadiyah Magelang, 2023)
Preparing students to be ready to compete in the 4.0 era using the implementation of the available curriculum is one of the teacher's tasks in the classroom. One of the problems that occurred in several elementary schools in Purworejo district was that learning still used conventional learning in the form of lectures and questions and answers, and the evaluation media used did not vary. For this reason, the introduction of interactive electronic game media based on QuizWhizzer can be the right solution as an evaluation tool. The purpose of this program is to increase teachers' understanding, knowledge, abilities and skills in creating interactive learning media using QuizWhizzer. The method used in this program is service learning with 3 stages, namely preparation, implementation and evaluation. This program was attended by 15 elementary school teachers who were held at the Sambeng Public Elementary School, Bayan sub-district, Purworejo Regency. The results obtained from this training are increased teacher understanding, abilities and skills in creating interactive and interesting evaluation tools.